DEVELOPING READING SKILLS TEACHING MATERIALS BASED ON THE SCIENTIFIC APPROACH FOR STUDENT OF MANSYAUL HUDA BOJONEGORO EAST JAVA - Dessy suryawati; Abdul Wahab Rosyidi (Universitas Islam Negeri Alauddin Makassar, 2023)
In accordance with the regulation of the Minister of Education and Culture No. 81 A 2013 Appendix VI regarding aspects of the 2013 Curriculum Scientific Approach which includes: Observing, Questioning, Exploring, Reasoning and Communicating. The learning concepts offered by the 2013 curriculum can be a new hope and challenge for learning Arabic. The end result is an increase and a balance between the ability to become good human beings (soft skills) and humans who have the skills and knowledge to live properly (hard skills) from students which include aspects of attitude, knowledge, and skills competencies. Based on this, the researchers developed teaching materials to support the 2013 Scientific Approach Arabic book used in schools to improve the Reading Skills of 4th grade MI students. Mansyaul Huda. So the researcher formulates the problem as follows: 1) How is the development of textbooks to improve reading skills with a scientific approach? 2) What is the feasibility of textbooks to improve reading skills with a scientific approach? 3) How is the validity (feasibility) of textbooks to improve reading skills with a scientific approach? . This study aims to 1) describe the process of making textbooks 2) describe the feasibility of textbooks 3) describe the validity of textbooks. This research uses a development methodology with the ADDIE.. In collecting data the researchers used the method of observation, interviews, documents, questionnaires and tests. In analyzing the data obtained from the questionnaire, the researcher used the linkert scale. The results of this study are: 1) The researcher applies the steps of the ADDIE method and implements the steps of the Scientific approach in the teaching materials 2) The value of the validity of the textbook is based on a material and language expert questionnaire with a percentage of 68%. design experts achieve a 100%. And the results of the validation of the Arabic language teacher reached a percentage of 92%. This shows that the developed textbook is suitable for use in learning Arabic. 3) This teaching material is said to be effective which can be proven by the t-test value of 10,146 which is greater than 2,056. With these results, it is known that the teaching materials for Arabic books to improve reading skills are good and feasible to be implemented in grade student elementary school IV